The Potential of 9,10-Anthraquinone in Inhibiting Human Cancer Cells Growth - Irmanida Batubara; Arif Rakhman Hakim; Silmi Mariya; Suminar Setiati Achmadi; Valentina Sokoastri; Agustin Sri Mulyatni; Rohayati Suprihatini (National Cancer Center - Dharmais Cancer Hospital, 2021)
Background: 9,10-Anthraquinone (9,10-AQ) is a contaminant on some agricultural products and considered as carcinogenic based on EU Regulation No. 1146/2014. Except for little evidence on experimental rats, there is no strong proof regarding the carcinogenicity in humans. Therefore, it is essential to find a safe dose of this compound since the difference in 9,10-AQ levels will affect cancer cell growth. This research aims to find the 9,10-AQ concentration that does not proliferate the human cancer cells under in vitro study.Methods: In determining the 9,10-AQ concentration that does not proliferate the cancer cells growth, 0.01 to 500 mg/L 9,10-AQ was directly tested on four human cancer cells (colorectal carcinoma HCT 116, colon adenocarcinoma WiDr, breast cancer MCF-7, and cervical cancer HeLa), and the viability of the cells was counted via (3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyl tetrazolium bromide) assay. In the gene expression level, the effects on a selected cancer cell line were determined by qRT-PCR against BAX, BCL-2, PCNA, and P53.Results: The result indicates that 9,10-AQ up to 500 mg/L concentration does not proliferate the cell’s growth but instead inhibits those four cancer cells’ growths. The concentration of 9,10-AQ that inhibits 50% the cancer cells growth (IC50) value was 321.8 mg/L (1.55 mM) against HCT 116 and above 500 mg/L (above 2.40 mM) against WiDr, MCF-7, and HeLa. The 9,10-AQ at 500 mg/L (or 2.40 mM) increases BAX expression and acts as an apoptotic agent on HeLa cells.Conclusions: The investigation has shown that 9,10-AQ up to 500 mg/L concentration does not proliferate the cancer cell growth; instead, it inhibits the HCT 116 and HeLa cells growth. We have preliminary evidence regarding the apoptotic mechanism of 9,10-AQ by increasing BAX gene expression on HeLa cells.